Small-signal stability, control and dynamic performance of power systems - Gibbard, M.J; Pourbeik, P; Vowles, D.J (University of Adelaide Press, 2015)
A thorough and exhaustive presentation of theoretical analysis and practical techniques for the small-signal analysis and control of large modern electric power systems as well as an assessment of their stability and damping performance.